An Educational Analysis of Rewards As Gratification for Employees: An Islamic Criminal Law Perspective - Muhammad Dhany Riansyah; Rizal; Hijriyana Safithri (Yayasan Azhar Amanaa Yogyakarta, 2026)
Gratification is a form of action that has the potential to lead to criminal acts of corruption if it is carried out by civil servants or state administrators related to their positions and authorities. This study aims to determine the analysis of rewards as gratification for employees (study of Law Number 20 of 2001 Article 12b paragraph (1) in conjunction with Law Number 31 of 1999 concerning criminal acts of corruption) and to determine the perspective of Islamic criminal law in the analysis of rewards as gratification for employees. This research is a normative juridical legal research, namely research conducted by examining library materials (library research), where the data used is library data that is related to this research which refers to legal norms, principles, rules of statutory regulations. The results of the study show that in positive law, gratification is strictly regulated in Law Number 31 of 1999 in conjunction with Law Number 20 of 2001, where any gratification received by civil servants (ASN, employees based on the Criminal Code, recipients of state salaries/state facilities) or state administrators (executive, legislative, judicial officials) is considered a bribe if it is contrary to their obligations or duties and must be reported to the Corruption Eradication Commission. Meanwhile, in the perspective of Islamic criminal law, gratification that contains elements of ulterior motives or aims to influence employee decisions is categorized as risywah (bribery) or ghulûl (treason) which is forbidden and includes major sins. Although giving gifts is basically encouraged in Islam, it becomes prohibited if it is related to certain positions and interests. Thus, both positive law and Islamic criminal law equally prohibit gratification that has the potential to damage justice, trust, and the integrity of state apparatus.